HUMAN LANGUGAGE ACQUISITION: THEORETICAL AND EMPIRAL PERSPECTIVES - Muxsinova Shaxzoda (Zamonaviy ta’lim va tilshunoslik rivoji, 2026)
This study examines major theoretical and empirical perspectives on human language acquisition. It analyzes the main approaches to language learning, including behaviorism, nativism, social interaction theory, statistical learning theory, and the critical period hypothesis. The research also explores recent neuroscientific findings concerning bilingualism and social interaction in language development. Using a mixed-methods approach, the study investigates language acquisition among children aged 18 months to 5 years through observations, standardized tests, and caregiver interviews. The findings demonstrate that language acquisition results from the interaction of biological predispositions, environmental exposure, cognitive mechanisms, and social communication. Special attention is given to the positive effects of bilingualism on cognitive flexibility, attentional control, and executive functioning. The study concludes that rich linguistic environments and active social interaction significantly enhance children’s language development and learning efficiency.